Illokutive Strukturen und Dialoganalyse Eine dialogisch begruendete und erweiterte Sprechakttheorie basierend auf Untersuchungen zur neueren tschechischen narrativen Prosa - Unrath-Scharpenack, Katrin (Specimina philologiae Slavicae, 2000)
The aim of this work is to describe dialog structures: dialogue structures that express different attitudes of interlocutors to the conversation and the partner. In addition, however, my hope is to be able to point out a possible way through the description of a dialogical attitude and the corresponding discussion structures, using specific "techniques" so structured and structured conversations that they lead to real understanding and thus to an improvement of the culture of dialogue.